(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The Iron Quadrangle of Minas Gerais, Brazil has suffered disastrous socioeconomic and environmental consequences due to predatory extractive activities such as mining. A diversified development model that takes into account social, cultural, environmental, and institutional factors is urgently needed. This Participatory-Action-Research project aims to promote agroecological territorialization in the peasant communities of Itabirito, Mariana, and Ouro Preto using the Farmer-to-Farmer Social Methodology as an instrument for the project development, to foster economic diversification and sustainable land use, thus strengthening agroecological production.